THE PREVALENCE OF USING ASPIRIN BY DIABETIC PATIENTS VISITING PRINCE RASHID HOSPITAL - Al -Tarawneh, Suhair Shaher; Alhroot, Arwa Ali; Abu Jama’ah, Wafa’a Jamil; Alsabra, Tariq Mufeed; Al Madadha, Raeda Abdel wahab; Abeeleh, Jaafar Abu (European Scientific Journal, ESJ, 2015)
Introduction: Diabetes has various health impacts including inflammatory processes. Aspirin is used as anti-inflammatory treatment. Study objectives: to study the prevalence of aspirin use among diabetic patients. Methods and subjects: a retrospective study design was employed to collect data from study participants who attended internal medicine clinics at Rashid Prince Hospital. A total of 447 files of diabetic patients were reviewed. Study variables included age, gender, body mass index, aspirin intake, cardiac diseases, family history of cardiac diseases, and family history of diabetes. Data were analyzed using SPSS version 20. Study findings: the mean age of participants was 55.58+ 10.46 years, 47% of participants were males, and the mean of BMI was 39.18 which implied that participants in general were obese. Aspirin intake was reported by 43% of participants, about 76% of participants had cardiac disease, about 63% of patients had a family history of cardiac disease, and 31% had a family history of diabetes. Aspirin intake was associated significantly with gender (P=0.001) and females were more likely to intake aspirin. No other significant association was observed between aspirin intake and other study variables. Conclusion: the study findings showed that 43% of diabetic patients received aspirin as a treatment, while diabetic patients who had cardiac problems were 76% which implies that the prescription policy of aspirin needs to be revised.